The Effect of Using Hot Chair Strategy on ‎Improving Oral Expression Skills - Al-Bari, Qasim (Jordan Journal of Educational Sciences, 2021)
The current study aimed to investigate the effect of hot chair strategy on improving oral expression skills among seventh-grade students in Jordan. A quasi-experimental method was used. The sample of the study comprised (32) seventh basic grade students from first basic Rawdat Al-Amirah Bassma for girls school of Western Northern badia directorate of education who were selected and divided into two groups: experimental (16 students) and control (16 students). To achieve the purposes of the study, a checklist scale for improving oral expression skills was developed.An oral expression test was prepared.Validity and reliability of the test were ensured. Every student was assessed in light of the criterion prepared for this purpose. A pre/post-test was administered for both groups. The results of the study showed that there was a statistically significant difference in favor of the experimental group that was taugh using the hot chair strategy